Axonal excitability in X-linked dominant Charcot Marie Tooth disease - Liang, Christina; Howells, James; Kennerson, Marina; Nicholson, Garth A.; Burke, David; Ng, Karl (Clinical neurophysiology, 2014)
•X-linked Charcot–Marie–Tooth disease type 1 patients have a nerve excitability profile that distinguishes them from other chronic demyelinating neuropathies.•These changes are not correlated with the severity of the neuropathy, nor do they seem to depend on the underlying mutation.•The mathematical model suggests changes explicable by a mixed axonal and demyelinating picture. We investigated peripheral nerve function in X-linked Charcot–Marie–Tooth disease type 1 (CMTX1), and considered the functional consequences of mutant connexin-32. Twelve subjects (9 female, 3 male) were assessed clinically, by nerve conduction and excitability studies. A model of myelinated axon was used to clarify the contributing changes. All subjects had abnormal nerve conduction. Excitability studies on median nerve axons showed greater threshold changes to hyperpolarising currents, with “fanning out” in threshold electrotonus, and modest changes in the recovery cycle. Modelling suggested shortening of internodal length, increase in nodal fast potassium currents, shift of the voltage activation hyperpolarisation-activated cyclic-nucleotide-gated channels, and axonal hyperpolarisation. Plotting threshold versus extent of hyperpolarising threshold change in threshold electrotonus distinguished the CMTX1 patients from other chronic demyelinating neuropathies reported in the literature except hereditary neuropathy with pressure palsies (HNPP). Some measures of axonal excitability are similar in CMTX1 and HNPP (though not the recovery cycle), but they differ from those in other chronic demyelinating neuropathies. The findings in CMTX1 are consistent with known pathology, but are not correlated to neuropathy severity. The findings in CMTX1 could be largely the result of morphological alterations, rather than plasticity in channel expression or distribution.